Immunological state of adult germfree miniature Minnesota pigs - Trávnícek, J; Mandel, L; Trebichavský, I; Talafantová, M (Folia microbiologica, 1989)
Fundamental hematological and immunological data were obtained on sexually mature germfree miniature pigs fed, after the milk diet period, with cereal-type diet sterilized by gamma-radiation, and were compared with data of control conventional animals. Germfree adult pigs had a lower count of peripheral blood leukocytes with a lower percentage of neutrophil granulocytes and without any younger forms, a lower total serum protein level with a negligible amount of gamma and alpha 2 globulin fractions and a higher serum albumin and beta globulin level. In the mesenteric lymph nodes and in spleen, surface IgA-bearing cells predominated over surface IgG-bearing cells. Also a large amount of IgA-containing cells was found in the intestinal lamina propria, where the IgG cells were present in a negligible amount. IgM cells were the most frequent surface isotype in peripheral blood. The count of blood T lymphocytes was more than doubled.
Keywords: gnotobiologické modely; prasata; Swine; Immune System; Male; Germ-Free Life; granulocyty; mužské pohlaví; Swine, Miniature; imunoglobuliny; imunitní systém; leukocyty; Animals; ženské pohlaví; zvířata; Leukocytes; Granulocytes; Female; Immunoglobulins; miniaturní prasata